A Calculation Method of Fragment Number and Mass Distribution of Blast-fragmentation Warhead based on Neural Network. Issue 1 (July 2021) - Sun, Yong; Li, Jun; Liu, Dawei; Xue, Jirong; Guo, Zhiming
Abstract: The Mott distribution model is analyzed and deduced in this paper. On this basis, a calculation method of fragment number and mass distribution of blast-fragmentation warhead based on Neural Network is proposed. Based on the Mott distribution model, the empirical parameters in the Mott distribution model are determined by using the strong nonlinear mapping ability of BP neural network and the associative memory ability of external stimuli and input information Then, the number and mass distribution of fragments are determined, and the calculation speed and result accuracy are improved.